2018
DOI: 10.1111/exd.13698
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 attenuates a murine model of atopic dermatitis through inhibition of langerin‐positive DCs migration

Abstract: Atopic dermatitis (AD) is a common chronic inflammatory skin disease that is often associated with skin barrier dysfunction leading to a higher frequency of bacterial and viral skin infections. Toll-like receptor (TLR) 4 on resident skin cells was involved in sensing pathogens and eliciting pathogen-specific innate and adaptive immune responses. Previous studies have demonstrated that TLR4 was linked to AD severity in context of pathogen infection. However, the immune regulatory role of TLR4 in AD remains to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Furthermore, the single nucleotide polymorphisms (SNPs) related to oxidative stress and inflammation indicating that there was a close association between TLR2, TLR4, and TNF and traffic-related air pollution, and this revealed the geneenvironment interactions in the development of AD (85). In TLR4 -/mice, hapten (2,4-dinitrochlorobenzene)-induced AD symptoms and Th2-type inflammatory responses were more severe than wild-type mice and increased the migration of DCs into draining lymph nodes (86). This indicated that TLR4 mediated immune responses associated with AD development.…”
Section: Toll-like Receptors Signaling In Admentioning
confidence: 99%
“…Furthermore, the single nucleotide polymorphisms (SNPs) related to oxidative stress and inflammation indicating that there was a close association between TLR2, TLR4, and TNF and traffic-related air pollution, and this revealed the geneenvironment interactions in the development of AD (85). In TLR4 -/mice, hapten (2,4-dinitrochlorobenzene)-induced AD symptoms and Th2-type inflammatory responses were more severe than wild-type mice and increased the migration of DCs into draining lymph nodes (86). This indicated that TLR4 mediated immune responses associated with AD development.…”
Section: Toll-like Receptors Signaling In Admentioning
confidence: 99%
“…In contrast to our results, the upregulation of TLR4 expression may be related to modulation of AD development as well as protection of infection. Deficiency of TLR4 induces the aggravation of AD after 2,4-dinitrochlorobenzene (DNCB) administration, via increased Th2 responses (22). In addition, TLR4 suppresses the pathogenic mechanism of AD induced by Aspergillus fumigatus extracts (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have reported that TLR4 is a negative regulator in the pathogenic mechanism of AD. Deletion of TLR4 suppresses AD-like symptoms and skin inflammation in AD-like mice due to fungus allergens and 2,4-dinitrochlorobenzene (DNCB) (20)(21)(22). Der p 2 does not induce AD via TLR4, but through TLR2 (23).…”
Section: Introductionmentioning
confidence: 99%
“…The use of mouse lines to label and conditionally disrupt genes in SCs can then be adapted to the established mouse models of psoriasis and AD. [ ] Given the findings that global p75NTR KO alters the cutaneous inflammatory response, SC‐specific deletion of p75NTR (eg Plp‐CreER T2 p75NTR lox/lox ) should be done to validate the role of SC p75NTR signalling in these disease models. Finally, mouse lines that allow conditional disruption of SC activation are already existing (eg Plp‐CreER T2 Sox10 lox/lox ).…”
Section: Discussionmentioning
confidence: 99%